PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK PURBASARI DI JAKARTA TIMUR - Alfina Ramawati; Amanda Setiorini (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
This study was conducted to determine the effect of brand image and price on purchasing decisions either simultaneously or partially on Purbasari Cosmetic Products in East Jakarta. The sampling technique in this study was carried out by the accidental sampling technique. The sample used in this study was 100 respondents who were taken from the population of consumers or buyers of Purbasari Cosmetics Obtaining data using a questionnaire with a differential semantic scale. Data analysis in this study is quantitative using multiple linear regression. The results of tests conducted, it was found the fact that Brand Image and Price simultaneously have a positive and significant influence on purchase decisions.